EXPLORING TOURISM POTENTIAL AND MARKETING STRATEGIES TO IMPROVE THE ECONOMY IN JAYAWIJAYA REGENCY, PAPUA - Tiomy Butsianto Adi; Fakhruddin Kurnia M (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
: Jayawijaya is a region that has traditional culture that still exists in the current era of globalization and will officially be 67 years old on December 10 2023. As one of the districts in the central mountainous region, it should be able to compete with other districts and cities, especially in terms of tourism. The contradiction felt in the last decade is that Jayawijaya has lost its attraction for local people and foreign tourists to come to visit. The aim of this research is to explore the potential of tourism that is oriented towards local wisdom values and environmental and cultural preservation, based on local communities (community based tourism), including marketing strategies for tourist attractions to provide economic benefits for the community in the long term. Specifically, this research is to find out and understand several things in order to formulate strategies in solving the problem of competitive and sustainable tourism potential.